The inositol phosphatase SHIP2 enables sustained ERK activation downstream of FGF receptors by recruiting Src kinases - Fafilek, Bohumil; Balek, Lukas; Bosakova, Michaela Kunova; Varecha, Miroslav; Nita, Alexandru; Gregor, Tomas; Gudernova, Iva; Krenova, Jitka; Ghosh, Somadri; Piskacek, Martin; Jonatova, Lucie; Cernohorsky, Nicole H; et al. (Science signaling, 2018)
Sustained activation of extracellular signal-regulated kinase (ERK) drives pathologies caused by mutations in fibroblast growth factor receptors (FGFRs). We previously identified the inositol phosphatase SHIP2 (also known as INPPL1) as an FGFR-interacting protein and a target of the tyrosine kinase activities of FGFR1, FGFR3, and FGFR4. We report that loss of SHIP2 converted FGF-mediated sustained ERK activation into a transient signal and rescued cell phenotypes triggered by pathologic FGFR-ERK signaling. Mutant forms of SHIP2 lacking phosphoinositide phosphatase activity still associated with FGFRs and did not prevent FGF-induced sustained ERK activation, demonstrating that the adaptor rather than the catalytic activity of SHIP2 was required. SHIP2 recruited Src family kinases to the FGFRs, which promoted FGFR-mediated phosphorylation and assembly of protein complexes that relayed signaling to ERK. SHIP2 interacted with FGFRs, was phosphorylated by active FGFRs, and promoted FGFR-ERK signaling at the level of phosphorylation of the adaptor FRS2 and recruitment of the tyrosine phosphatase PTPN11. Thus, SHIP2 is an essential component of canonical FGF-FGFR signal transduction and a potential therapeutic target in FGFR-related disorders.
Keywords: aktivace enzymů; Animals; MAP Kinase Signaling System; Cell Line, Tumor; Protein Tyrosine Phosphatase, Non-Receptor Type 11; Adaptor Proteins, Signal Transducing; Enzyme Activation; HEK293 Cells; adaptorové proteiny signální transdukční; vazba proteinů; lidé; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Receptors, Fibroblast Growth Factor; membránové proteiny; HEK293 buňky; Phosphorylation; Humans; fosforylace; fosfatidylinositol-3,4,5-trisfosfát-5-fosfatasy; skupina kinas odvozených od src-genu; src-Family Kinases; receptory fibroblastových růstových faktorů; Membrane Proteins; tyrosinfosfatasa nereceptorového typu 11; zvířata; extracelulárním signálem regulované MAP kinasy; Protein Binding; MAP kinasový signální systém; nádorové buněčné linie; Extracellular Signal-Regulated MAP Kinases